Jordanians’ youth Fears and their Relationship to Some Variables - Al-Harhasha, Salem A .S. (Journal of Social Sciences (COES&RJ-JSS), 2019)
The present study aims at identifying the fears of Jordanian youth. The sample included (255) young male and female. The study tool validity was confirmed by using the coefficient of internal consistency of(0.94). The results indicated that the total average mean of the degree of fear among Jordanian youth reached (3.15) and by percentage of (63%). In addition, there were statistically significant differences in the level of fearamong the youth related to the gender variable (males and females) at the level of alpha (α = 0.05),in favor forfemales. There were statistically significant differences at the level of (α = 0.05) between self-fears and social fears, and favor of the social fears, while there were no statistically significant differences attributed to the variable of age and the institution of education. Further, the researcher recommends conducting further studies that addressing the youth needs and psychological pressures, and building a training programs and guidance;in order to face those fears.